COVID-19 vaccine hesitancy in Sweden and Italy: The role of trust in authorities. Issue 6 (August 2022) - Raffetti, Elena; Mondino, Elena; Di Baldassarre, Giuliano
Background: The success of vaccination campaigns against COVID-19 infection is vital for moving from a COVID-19 pandemic to an endemic scenario. We aimed to unravel the influence of the risk perception of epidemics along with individual and contextual factors on adherence to COVID-19 vaccination campaigns in Italy and Sweden. Methods: We compared the results of two nationwide surveys carried out in August 2021 across four domains of epidemic risk perception: perceived likelihood, perceived impact on the individual and perceived individual and authority knowledge. The roles of individual and contextual determinants were also explored. Results: The survey included 2144 participants in Sweden (52.3% women) and 2010 in Italy (52.6% women). In both countries, we found that trust in authorities was one of the main drivers of this process, with two-fold increased odds of being vaccinated. Being highly educated and having a higher relative income were associated with a higher adherence to the vaccination campaign (for relative income OR = 1.44, 95% CI 1.23–1.67 in Sweden and OR = 1.18, 95% CI 1.04–1.34 in Italy; for education OR = 1.90, 95% CI 1.30–2.77 in Sweden and OR = 1.47, 95% CI 1.09–1.97 in Italy), whereas a right and centre-right compared with a left and centre-left political orientation was negatively related to vaccination adherence (OR = 0.41, 95% CI 0.25–0.67 in Sweden and OR = 0.47, 95% CI 0.33–0.68 in Italy). Conclusions: Increasing trust in authorities, along with an equal global distribution of vaccine doses, can contribute to accelerating vaccination campaigns around the world and, in turn, to move towards an endemic scenario.